Farmers’ Use of Agricultural Information and Influencing Factors: The Case of a Selected Community Radio Station in Coastal Bangladesh - Rashid, Md Mamun ur; Liza, Farzana Yesmin (Journal of the Bangladesh Agricultural University, 2025)
Timely and need-based information is a crucial precursor in informed decision-making. Community radio serves as a vital avenue for farmers who lack access to mainstream media. However, the use of community radio by farmers for agricultural purposes remains unclear due to a paucity of empirical information. This research investigated the use of community radio (CR) for delivering agricultural information to farmers and the associated factors influencing its use. Therefore, the study employed a mixed-methods approach and randomly selected 278 respondents from the coverage area of a community radio station in Barguna District, Bangladesh. Data were collected through face-to-face structured interviews. Focus group discussions and key informant interviews were also conducted with purposefully selected samples. The use of CR was measured adopting a five-point rating scale (Always 5…… Never 1) against 14 items. The findings reveal that, despite being mandated to provide need-based agricultural information, the time allocated for agricultural programs on the radio is minimal, averaging only 2 hours and 35 minutes per week. Among respondents, 71% listen to CR agricultural programs from rarely to very regularly, while 29% do not listen at all. According to the respondents, the participation of community members, particularly farmers, in radio programs is virtually non-existent. They primarily use CR information for decision-making regarding disease and pest management (WM = 0.633), determining fertilizer doses and application methods (WM = 0.546), and receiving weather information (WM = 0.543). Logistic regression results indicate that age, cultivable land, income from agriculture, access to CR radio, and the network strength of CR significantly influence respondents' usage of CR. This research recommends increasing the number of agricultural programs on community radio (CR) through consistent budget allocation while incorporating more farmer-participatory initiatives. Additionally, a targeted campaign aimed at elderly farmers should be implemented to enhance their interest in CR, ultimately improving their access through a strengthened network. J Bangladesh Agril Univ 23(3): 366–376, 2025